MR imaging in idiopathic growth hormone deficiency. - Hamilton, J; Blaser, S; Daneman, D (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE MR imaging findings of one or more of the following has been suggested to be a sensitive and specific indicator of hypopituitarism: small anterior pituitary gland, attenuated or absent pituitary stalk, and ectopic posterior pituitary. We hypothesized that these MR findings would be common in our group of patients with idiopathic isolated growth hormone deficiency (GHD) or multiple pituitary hormone deficiencies (MPHD) and would be a good indicator of the severity of the hypopituitarism.METHODS MR images were obtained for 35 patients with idiopathic GHD (20 with isolated GHD and 15 with MPHD; age range, 2 to 17 years) and analyzed to define one or more of the following triad of abnormalities: 1) small/absent anterior pituitary, 2) truncated/absent pituitary stalk, and 3) ectopic posterior pituitary, as well as for any other associated anomalies. The findings were correlated with the clinical and biochemical presentation.RESULTS Pituitary abnormalities were common in both groups (80% with isolated GHD, 93% with MPHD). We found a high frequency of midline CNS malformations, including optic nerve hypoplasia (9%), Chiari type I malformations (20%), and medial deviation of the carotid arteries (37%). Breech delivery, neonatal hypoglycemia, jaundice, micropenis, or single central incisor occurred equally with both isolated GHD and MPHD. In patients whose peak growth hormone level was less than 3 microg/L (n = 19), 90% had the MR triad, compared with 390% of those with growth hormone levels 3 microg/L or greater or less than 8 microg/L (n = 13) (P <.01). Almost all (92%) of those with ectopic posterior pituitary had anterior pituitary heights less than -2 SD for age.CONCLUSION MR abnormalities were common in children with both isolated GHD and MPHD and were closely associated with peak growth hormone levels less than 3 microg/L. The presence of other CNS and clinical findings (eg, single central incisor and micropenis) supports the theory of an embryologic defect as the cause of the pituitary abnormalities.